The effectiveness of a tele-intensive care unit implementation at a secondary hospital in Eastern Saudi Arabia - Aloraini, Muhannad (International Journal Of Community Medicine And Public Health, 2017)
Background: Tele-intensive care units (tele-ICUs) are promising medical solutions for improving critical care quality, enhancing access to health care, and increasing the productivity of intensivists. King Faisal Specialist Hospital and Research Center (KFSHRC) initiated a tele-ICU implementation in Saudi Arabia during 2009/2010, with the aim of creating 28 tele-ICU-connected hospitals throughout the region by 2014. However, the effect of tele-ICUs on patient outcomes remains unclear. This study assessed the effectiveness of a tele-ICU intervention program on patient outcomes. Methods: A retrospective pre-post study was performed in an adult medical-surgical ICU at a secondary hospital in Eastern Saudi Arabia. Tele-intensivists were located at the KFSHRC. The sample comprised adult patients (≥12 years, as per hospital policy) admitted to the ICU. Patients were allocated into pre-intervention (January 1 to April 29, 2012) and post-intervention (May 1 to August 31, 2012) groups; each group had 178 patients. The tele-ICU was implemented on April 30, 2012. Results: According to a Mann–Whitney U-test, the groups did not differ on length of stay (LOS) (U=16097.50, p=0.78). Medians and interquartile ranges in length of stay for both groups were 2 days. Regarding mortality, 10 (5.6%) pre-intervention patients died, while 12 (6.7%) post-intervention patients died. This difference was not significant (p=0.51). Conclusions: The tele-ICU program did not appear to impact patient outcomes in terms of mortality or LOS.